Dialogues with traditional people and cultural diversity at the XV Capixaba Seminar on Art Teaching - Guimarães, Aissa Afonso; Siqueira, Jane Seviriano (Farol, 2024)
This paper is inspired by the 2nd Conference entitled “Povos Originários”, held at XV Seminário Capixaba do Ensino da Arte, at the Federal University of Espírito Santo. Urgent dialogues was the theme of the seminar, to name the need to debate emerging themes in contemporary times, such as issues related to original peoples, and the need to establish dialogue with subjects who have knowledge of non-formal education. First, we highlight the process of transmitting knowledge in traditional culture, based on a "Ponto de Memória" in a quilombola community in the north of ES. Secondly, we commented on the relevance of women in this process. Thirdly, we examine articulations between teaching-learning and traditional culture, in the context of popular arts. Considering the dialogues at the Conference, we pointed out that collaborative work with masters of traditional culture would contribute to the inclusion of indigenous, african and afro-brazilian history and culture in formal education, at all levels. We echo the demand for the inclusion of young indigenous and black quilombolas in schools and universities as a democratic principle of the right to life, which involves the inclusion of cultural diversity in debates in these spaces.
Keywords: Popular arts; Masters of Knowledge; Traditional Culture